Analysis of application-based learning media development needs android on volleyball game - Destriani, Destriani (Department of Physical Education, Sport, Health and Recreation, 2021)
This study aims to analyze the need for developing learning media based on android applications in volleyball game learning. This research method uses a survey through filling out questionnaires distributed via google form. The number of respondents in this study were 110 students of physical education and health study programs. The results showed that 100% of students stated that they needed varied learning media, 92.7% of students needed smartphones in volleyball learning, 80.1% of students stated that smartphones made it easier for students to support the volleyball learning process, and 92.1% students need an android application for learning volleyball games. Based on the results of this analysis, it can be seen that the development of learning media based on android applications in volleyball games is needed for learning volleyball games, which can later be used as one of the learning media in volleyball games.